Activity patterns of the water opossum Chironectes minimus in Atlantic Forest rivers of south-eastern Brazil. (4th April 2013) - de Souza Leite, Melina; Queiroz, Thiago Lopes; Galliez, Maron; de Mendonça, Patrícia Pinto; Fernandez, Fernando A. S.
Abstract: The activity of the water opossum Chironectes minimus was studied in Atlantic forest rivers in south-eastern Brazil using radiotracking, from October 2004 to October 2008. There were 439 nocturnal fixes of 11 males and four females. Activity patterns of the water opossum were compared among sexes and seasons, using linear and generalized linear mixed models. The water opossum is active mostly at night, showing a unimodal pattern, with activity increasing after sunset and decreasing thereafter along the night. Females were more active in the first quarter of the night and males in the second one. The activity period of males was longer in the dry season, while for females it was longer in the wet season. Sex and season were important determinants of the water opossum activity patterns, mainly because of different sex strategies in a promiscuous/polygynous mating system. However, despite those influences the overall distribution of activity along the night was similar to most Neotropical marsupials. Therefore, similarities in the activity patterns are probably due to phylogenetic constraints and to the absence or weakness of selective pressures modifying the activity of the water opossum.